Analisis Statistik Dalam Manajemen Rekrutmen Dan Seleksi Pegawai: Tinjauan Literatur - Mozin, Sri Yulianty; Liputo, Nadila; Latif, Fatmawati; Ntelu, Nurferawati; Salihi, Tiara Kasih (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
A successful organization is one with professional and competent employees. therefore, employee recruitment and selection management becomes an important point to pay attention to and analyze more deeply. however, it cannot be denied that there are still some organizations that have difficulties in statistical analysis of recruitment and selection management, for example in terms of choosing and determining the appropriate method to apply. With this background, the researcher in this article examines statistical analysis in employee recruitment and selection management through literature review. in this research, the literature study method or literature review is the choice of researchers. the results found show that employee recruitment and selection have a positive and significant influence on employee performance in organizations in both the public and private sectors.